Storage of 'Espada' mango fruits in modified atmosphere and cooling: effects on conservation - Galli, Juliana Altafin; Bernardes Soares, Maria Beatriz; Melo Martins, Antonio Lucio; Galli, Julio Cesar [UNESP] (Edp Sciences S A, 2013)
Introduction: Brazil is a major producer of mangoes, but the export volume is still small because of the short shelf life of this fruit. The objectives of our work were to evaluate the effect of modifying the storage atmosphere using plastic film and temperature, according to different periods of storage, on the characteristics of Espada mango grown organically. Material and methods. Seven treatments were applied to the fruits after their harvest: fruits stored at room temperature; at 12 degrees C / 80-90% relative humidity (RH); washed and stored at room temperature; washed and stored at 12 degrees C / 80-90% RH; washed, packed in PVC and stored at room temperature; washed, packaged in PVC and stored at 12 degrees C / 80-90% RH; and fruits harvested on the same day of evaluations, at (5, 9, 13, 16 and 21) days of storage. Results and discussion. Storage at 12 degrees C and 80-90% RH was more efficient in delaying fruit ripening, with minor evolution of peel and pulp color and soluble solids contents; this treatment also delayed the development of anthracnose. Fruits packed in PVC and stored at room temperature kept the peel and pulp color for 13 days, compared with 9 days for non-packaged fruits. The ideal time to harvest the Espada variety occurs at 165 days after the onset of flowering, with an index of 3 for skin color (equal amounts of green and yellow) and pulp color (yellow pulp), and soluble solids of 8.5 degrees Brix. The low severity of anthracnose found at different evaluation times indicates the probable tolerance of the Espada variety to the pathogen.
Keywords: Brazil; Mangifera indica; fruits; postharvest ripening; controlled atmosphere storage; Keeping quality